TRANSLATION VARIATION OF SPEECH LEVEL IN BALINESE INTO INDONESIAN AND ENGLISH - Savitri, Putu Weddha; Dewi, A.A. Sg. Shanti Sari (International Journal of Linguistics and Discourse Analytics, 2019)
This article aims at analyzing the process occurred in translating words or phrases that contains speech level in Balinese into Indonesian and English. As we know, Balinese language recognized the use of speech level in communication that represents a respectful and polite attitude to the other person, whereas in Indonesian and English, the use of speech level is not too significant as in Balinese. These differences may cause difficulties in translation process because the translator has to maintain this element in the target language. The source of this study is the conversation in Balinese shadow puppet â€œSidapaksaâ€ translated by Natarina (2014) into Indonesian and English. This study used documentation methode in collecting the data, while the analysis was presented qualitatively and descriptively. The result showed that mostly there are loss of information in translating words or phrases which contain speech level meaning because Balinese used more variety of words that show the social status of the speakers. But between two target languages, Indonesian can preserved speech level more than its translation in English. It is because Balinese is closely similar with Indonesian (the same language family) than English.